Long-term consumption of a Mediterranean diet improves postprandial lipemia in patients with type 2 diabetes: the Cordioprev randomized trial. Issue 5 (23rd November 2018) - Gomez-Marin, Beatriz; Gomez-Delgado, Francisco; Lopez-Moreno, Javier; Alcala-Diaz, Juan F; Jimenez-Lucena, Rosa; Torres-Peña, Jose D; Garcia-Rios, Antonio; Ortiz-Morales, Ana M; Yubero-Serrano, Elena M; del Mar Malagon, Maria; Lai, Chao Q; Delgado-Lista, Javier; et al.
ABSTRACT: Background: Patients with type 2 diabetes (T2D) have an elevated postprandial lipemia (PPL) that has been associated with increased cardiovascular risk. Objective: We aimed to analyze whether the long-term consumption of 2 healthy dietary patterns is associated with an improvement in PPL and remnant cholesterol (RC) concentrations in patients with T2D. Design: We selected patients from the Cordioprev study who underwent oral fat load tests (FLTs) at baseline and the 3-y follow-up (241 patients with and 316 patients without T2D). Subjects were randomly assigned to receive either a Mediterranean diet rich in olive oil (MedDiet; 35% of calories from fat [22% monounsaturated fatty acids (MUFAs)] and 50% from carbohydrates) or a low-fat (LF) diet [<30% fat (12–14% MUFAs) and 55% of calories from carbohydrates]. Lipids were measured in serial bloods drawn at 0, 1, 2, 3, and 4 h after the FLT. Results: After 3 y of dietary intervention, patients with T2D showed an improvement in their PPL measured as postprandial triglycerides (TGs) ( P  < 0.0001), TG area under the curve (AUC) ( P  = 0.001), and TG-rich lipoproteins (TRLs-TG; P  = 0.001) compared with baseline. Subgroup analysis, based on the type of dietary intervention, showed that those T2D patients randomly assigned to the MedDiet presented a reduction in the TG AUC of 17.3% compared with baseline ( P  = 0.003). However, there were no differences for T2D patients randomly assigned to the LF diet ( P  > 0.05) or in patients without T2D ( P  > 0.05) regardless of the dietary intervention. In addition, the MedDiet induced a significant improvement in the RC AUC in patients with T2D ( P  = 0.04). However, there was no significant improvement in those following the LF diet. Conclusions: Our findings show that the long-term consumption of a MedDiet rich in olive oil improves PPL and RC concentrations mainly in patients with T2D. This trial was registered at clinicaltrials.gov as NCT00924937.